Adab Guru dan Murid dalam Pendidikan Menurut Perspektif Syeikh Muḥammad Khaṭīb Langgien: Analisis terhadap Kitab Dawā’ al-Qulūb min al-‘Uyūb: Rules of Conduct for Teachers and Students in Education from Syeikh Muḥammad Khaṭīb Langgien’s Perspective: An Analysis of Kitab Dawā’ al-Qulūb min al-‘Uyūb - Mamat, Mohd Anuar (Journal of Al-Tamaddun, 2023)
Acquisition of knowledge is very important in Islam and it is an obligation upon every Muslim. The educational process is spread continuously since the era of Prophet Muhammad PBUH until today. Therefore, there are many extensive works in philosophy of education and its implementation in educational activities, authored by Islamic scholars including Malay scholars. The treatises of Malay Islamic education are variety, comprehensive and based on adab. Hence, this article will discuss one of the treatises written by Malay Islamic scholar in the 19th Century, entitled Dawā’ al-Qulūb min al-‘Uyūb. It is written by Syeikh Muḥammad Khaṭīb Langgien, a well-known Islamic scholar in the field of Tarekat and Tasawuf in 19th Century. However, the background of Syeikh Muḥammad Khaṭīb Langgien and his treatise Dawā’ al-Qulūb min al-‘Uyūb has not been explored before. This article will analyse the rules of conduct for teachers and students in this treatise based on content analysis method to explain the Syeikh Muḥammad Khaṭīb Langgien’s perspective. After the discussion, there are 17 rules of conduct for teachers and there are 28 rules of conduct for student (11 in general and 17 in specific). This theme is very interesting to study nowadays because there are many issues regarding moral and ethics in educational system. The Syeikh Muḥammad Khaṭīb Langgien’s perspective on rules of conduct for teachers and student also relevant because his thought based on Tasawuf point of view and his experiences as Tarekat leader. These findings are important contributions of Islamic scholars to ensure the quality of Islamic teachers and students in order to face the challenges in ethical and moral crisis in education nowadays.